Proceedings of the 48th Design Automation Conference 2011
DOI: 10.1145/2024724.2024762
|View full text |Cite
|
Sign up to set email alerts
|

An exact algorithm for the construction of rectilinear Steiner minimum trees among complex obstacles

Abstract: In this paper, we present an exact algorithm for the construction of obstacle-avoiding rectilinear Steiner minimum trees (OARSMTs) among complex rectilinear obstacles. This is the first work to propose a geometric approach to optimally solve the OARSMT problem among complex obstacles. The optimal solution is constructed by the concatenation of full Steiner trees (FSTs) among complex obstacles, which are proven to be of simple structures in this paper. The algorithm is able to handle complex obstacles including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…As we can see, (8), (9), and (10) are all strictly increasing function with respect to d. If we shift EF up (i.e. towards the source), d will decrease and thus the delays from A to B, C and D will all decrease.…”
Section: Internal Tree Structures In An Optimal Solutionmentioning
confidence: 92%
See 1 more Smart Citation
“…As we can see, (8), (9), and (10) are all strictly increasing function with respect to d. If we shift EF up (i.e. towards the source), d will decrease and thus the delays from A to B, C and D will all decrease.…”
Section: Internal Tree Structures In An Optimal Solutionmentioning
confidence: 92%
“…Therefore, although routing over obstacles is possible, one should be aware of the signal integrity issue and avoid routing long wires on top of obstacles that may lead to complicated post-routing electrical fixups. One way to tackle this problem is to construct an obstacle-avoiding rectilinear Steiner minimum tree (OARSMT) [4][5][6][7][8][9][10]. However, avoiding all obstacles may result in an unnecessary resource overhead.…”
Section: Introductionmentioning
confidence: 99%
“…Make-Set(p) 8 insert p into HV 9 while not all pin-vertices are in the same set 10 (u, v) ← Nearest Components(HV , HE, V , E) In [12], the authors had shown that the 3D-VG has O(|VS| log 2 |VS|) vertices and edges, and can be constructed in O(|VS| log 3 |VS|) time. One O(log |VS|) factor of the number of vertices, the number of edges, and the time complexity results from the depth of recursion for Step 2-Step 4 of the 3D-VG construction.…”
Section: It Is Clear That For Each Edge E Of T R(e) Is Valid In R(imentioning
confidence: 99%
“…However, as the IC technology significantly increases the density of an IC chip, a modern IC design contains more and more hard IP cores, macro blocks, and pre-routed nets, which are referred to as obstacles in the routing process. Therefore, the obstacle-avoiding RSMT (OARSMT) problem has become very important and received lots of attention recently [1]- [8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the obstacle-avoiding RSMT (OARSMT) problem has become very important and received lots of attention recently [2]- [10].…”
mentioning
confidence: 99%